Genealogi dan Corak Studi Kalâm di Indonesia - Zuhri Zuhri (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2016)
The discourse of kalâm (Islamic theology) in Indonesia has its long historical root. The discourse has initially emerged alongside the process of the spread of Islam in Indonesia. The dynamics of the discourse among various segments of the Indonesian Muslim society have found their rhythm from time to time. It should be noted, however, that the discourse has not yet found its genealogical pattern. This article, therefore, attempts to find the genealogical foundation and the pattern of studies of kalâm in Indonesia together with its trends. The developing reasoning of kalâm in the mediaeval periods of Islam, i.e. after the 12th century, tended to be strong in terms of its orthodoxy compare to the discourse itself. This subsequently becomes a source of inspiration for the discourse of kalâm in Indonesia until nowadays. As a result, there has been a sort of general trend that the study of kalâm in Indonesia has remained stagnant. It can be, among other, observed from the process of studying kalâm as knowledge reference, its development and formalization, and critique of the discourse, which indicate unprosperous condition for the discourse itself.